If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + -4x + -4 = x + -4 + x Reorder the terms: -3 + -4 + -4x = x + -4 + x Combine like terms: -3 + -4 = -7 -7 + -4x = x + -4 + x Reorder the terms: -7 + -4x = -4 + x + x Combine like terms: x + x = 2x -7 + -4x = -4 + 2x Solving -7 + -4x = -4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -7 + -4x + -2x = -4 + 2x + -2x Combine like terms: -4x + -2x = -6x -7 + -6x = -4 + 2x + -2x Combine like terms: 2x + -2x = 0 -7 + -6x = -4 + 0 -7 + -6x = -4 Add '7' to each side of the equation. -7 + 7 + -6x = -4 + 7 Combine like terms: -7 + 7 = 0 0 + -6x = -4 + 7 -6x = -4 + 7 Combine like terms: -4 + 7 = 3 -6x = 3 Divide each side by '-6'. x = -0.5 Simplifying x = -0.5
| -99=11s | | z/9-1=1 | | 4y-x^2y+2-x=0 | | (2x-3z)(8x-z)= | | m+15=5 | | ((40*15)+(x*15*1.5))*52=70000 | | 2p-5=17 | | x-1/3=-1/12 | | 0.30x+0.15y=10 | | 7x+14=91 | | x+(x*.481)=33400 | | y=151.2-22.4x | | (7x-6)(2x+3)=0 | | 7x+4.5y=50.5 | | xa+9=3x+b | | X-1/3=11 | | n^2+18n=-5 | | -14w-3-5w= | | 3x+28=4x+16 | | ((40*15)+(x*15*1.5)*52)=70000 | | 8x+25=6x+23 | | 0.30x+0.15y=40 | | (x)+(2x)+(3x)=102 | | -3n+4=-89 | | 2x+3x+7x=0 | | 9(x+8)+2=74 | | 6t+15t-12=24+-60 | | 4(x-4)+56=-4 | | -5(x-1)+12=-18 | | -3n+2-5n-7= | | [C-450]/=35 | | 3(x-2)+20=26 |